Nurses’ Knowledge in the Prevention and Management of Nasointestinal Tube Obstruction: A Cross Sectional Study - Wang L; Hou W; Liu Z; Chen L; Lin R; Huang Y (Risk Management and Healthcare Policy)
Lun Wang,1,2 Wanling Hou,1 Zhong Liu,2 Li Chen,2 Ruidua Lin,2 Yinying Huang1 1Department of Nursing, Women and Children’s Hospital, School of Medicine, Xiamen University, Xiamen, Fujian Province, People’s Republic of China; 2Neurosurgery Department, Zhong Shan Hospital, Xiamen University, Xiamen, Fujian Province, People’s Republic of ChinaCorrespondence: Wanling Hou, Department of Nursing, Women and Children’s Hospital, School of Medicine, Xiamen University, 10 Zhen Hai Road, Si Ming District, Xiamen, Fujian Province, People’s Republic of China, Tel +8613705033186, Email hwldyx2007@126.comBackground: The nasointestinal tube is a route of nutritional support for patients and maintaining patency is essential. Given the key role nurses play in the management and monitoring of these tubes, they need to have sufficient knowledge and skills to ensure the safety and well-being of the patients.Objective: To investigate the status quo of nurses’ knowledge of prevention and management of nasointestinal tube obstruction in six hospitals, and to analyze the influencing factors.Methods: A cross-sectional survey was conducted using the convenience sampling method, applying a general information questionnaire and a questionnaire on knowledge of prevention and management of nasointestinal tube obstruction.Results: A total of 268 valid questionnaires were collected. The mean score for nurses’ knowledge was 47.65± 4.09 out of a maximum possible score of 60 points on the questionnaire, with the score for storage and use of nutritional solutions being the lowest. The univariate analysis showed that there were statistically significant differences in the knowledge scores of nasointestinal tube prevention and management among nurses with different age, educational background, professional title, hospital grade, department, length of exposure to nasointestinal tubes, qualification of nasointestinal tube placement, and training experience. The multiple linear regression analysis showed that professional title, department and training experience were the influencing factors of nurses’ knowledge of nasointestinal tube obstruction prevention and management. Specifically, nurses with higher professional titles, more training experiences, or those working in intensive care units and surgical departments were more likely to achieve higher total knowledge scores in the prevention and management of nasointestinal tube occlusion.Conclusions: : The study shows that nurses’ knowledge of nasointestinal tube obstruction prevention and management is in the upper-middle level. Nursing managers should strengthen systematic training and improve interdepartmental exchange to promote young nurses’ knowledge and quality of nasointestinal tube care.Keywords: knowledge, nasointestinal tube, prevention, management, obstruction